Capital Gains and Dividend Taxes in Firm Valuation: Evidence of Triple Taxation - Collins, Julie H.; Kemsley, Deen (The Accounting Review, 2000)
Although firms account for entity-level taxes, they do not account for shareholder-level capital gains and dividend taxes. To account for these proprietary-level taxes, we add them to a residual-income equity valuation model. Empirical analysis supports the model's predictions. First, both capital gains and dividend taxes reduce investors' implicit valuation of the reinvested portion of earnings. Second, dividend taxes reduce the valuation of the portion of earnings distributed as dividends, but capital gains taxes do not. Third, dividend taxes reduce the valuation of retained earnings equity, but again, capital gains taxes do not. These findings suggest that investors implicitly extend entity-level accounting to the proprietary level when they value the firm. The findings also suggest that when fully accounting for the effects of implicit dividend taxes, reinvested earnings appear to be subject to three levels of taxation—corporate, dividend, and capital gains taxes. Paying earnings out as dividends eliminates the capital gains layer of tax and may provide a net wealth benefit for shareholders, rather than a tax penalty as commonly assumed.